2013
DOI: 10.1155/2013/141983
|View full text |Cite
|
Sign up to set email alerts
|

Positron Emission Tomography—Computer Tomography Scan Used as a Monitoring Tool Following Cellular Therapy in Cerebral Palsy and Mental Retardation—A Case Report

Abstract: Cerebral palsy (CP) is one of the non-progressive neurological diseases caused by damage to the brain tissue at birth, which leads to physical, cognitive and perceptive symptoms. Even after lifelong medical and therapeutic management there are residual deficits which affect the quality of life of the patients and their families. We examined a maximally rehabilitated, 20 year old male suffering from CP and Mental Retardation (MR). He had diplegic gait and Intelligence Quotient (IQ) score of 44 with affected fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Currently, cellular therapy has gained attention due to its neurorestoration abilities. Variety of cells comprising of embryonic stem cells, adult stem cells, umbilical cord blood cells, and induced pluripotent stem cells have been explored as a therapeutic option for neurological disorders including stroke, Alzheimer's and Parkinson's diseases, spinal cord injury, autism, and cerebral palsy [4–7]. Numerous preclinical studies have reported that these cells ameliorate the functional deficits in animal models of cerebral palsy [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, cellular therapy has gained attention due to its neurorestoration abilities. Variety of cells comprising of embryonic stem cells, adult stem cells, umbilical cord blood cells, and induced pluripotent stem cells have been explored as a therapeutic option for neurological disorders including stroke, Alzheimer's and Parkinson's diseases, spinal cord injury, autism, and cerebral palsy [4–7]. Numerous preclinical studies have reported that these cells ameliorate the functional deficits in animal models of cerebral palsy [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously published data wherein autologous mononuclear cell transplantation was carried out in children with various incurable neurological disorders including autism, cerebral palsy and mental retardation. Improvements were reported in quality of life of these patients [12][13][14]. On repeating and comparing the PET scan of brain after six months post therapy, significant changes were recorded and correlated to symptomatic improvements.…”
Section: Discussionmentioning
confidence: 93%
“…We have also published three case reports demonstrating the safety and efficacy of BMMNC transplantation in cerebral palsy [36,37,39]. In these case reports, the functional improvements are supported by improved brain metabolism recorded in comparative PET-CT scans performed before and after the intervention.…”
Section: Physical Disabilities -Therapeutic Implicationsmentioning
confidence: 94%
“…However, in 2015, we published a report of a 13-year-old boy with intellectual disability who exhibited improvements after stem cell therapy [70]. He was followed up after 3 and 6 months of intervention.…”
Section: Clinical Evidencementioning
confidence: 99%